2021
DOI: 10.1177/10634266211028199
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perspectives on Guided Parent-Delivered Cognitive Behavioral Therapy for Childhood Anxiety Disorders: A Qualitative Study

Abstract: Cognitive behavioral therapy (CBT) is an effective treatment for child anxiety disorders. Low-intensity forms of CBT, such as guided parent-delivered CBT (GPD-CBT), have been developed to increase access; however, it is unclear why some children benefit from this treatment and others do not. This qualitative study aimed to increase understanding of parents’ experiences of GPD-CBT and what facilitates and creates barriers to good outcomes. The sample was derived from a sample of families who took part in long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Clinician: 'I was nervous, and slightly intimidated, to work with parents before : : : I thought that because I didn't have children myself, they would question how I could understand : : : ' It can feel daunting to work with parents, especially for clinicians with limited experience, but as noted above, similar outcomes have been found when parent-led CBT was delivered by novices or by more experienced practitioners (Thirlwall et al, 2013). Qualitative interviews from the same study indicated that although some parents may have been initially surprised at being so involved in the treatment, they found the approach acceptable, reported empowerment and skill development, and identified wide-ranging benefits both for the child and the wider family (Allard et al, 2021). Clinicians have also described parent-led CBT as an 'empowering' and 'practical' approach (Evans et al, 2019) with high satisfaction reported by clinicians from a range of professional backgrounds when delivered to families individually (Creswell et al, 2010) and in groups (Evans et al, 2019).…”
Section: Lack Of Experience In Working With Parents/carersmentioning
confidence: 57%
See 2 more Smart Citations
“…Clinician: 'I was nervous, and slightly intimidated, to work with parents before : : : I thought that because I didn't have children myself, they would question how I could understand : : : ' It can feel daunting to work with parents, especially for clinicians with limited experience, but as noted above, similar outcomes have been found when parent-led CBT was delivered by novices or by more experienced practitioners (Thirlwall et al, 2013). Qualitative interviews from the same study indicated that although some parents may have been initially surprised at being so involved in the treatment, they found the approach acceptable, reported empowerment and skill development, and identified wide-ranging benefits both for the child and the wider family (Allard et al, 2021). Clinicians have also described parent-led CBT as an 'empowering' and 'practical' approach (Evans et al, 2019) with high satisfaction reported by clinicians from a range of professional backgrounds when delivered to families individually (Creswell et al, 2010) and in groups (Evans et al, 2019).…”
Section: Lack Of Experience In Working With Parents/carersmentioning
confidence: 57%
“…As shown in Table 1, parent-led CBT has commonly been delivered in groups. While this may bring advantages from peer support for some parents, this format may also introduce barriers for others (Allard et al, 2021). From our interactions with clinical teams we are aware that groups are often used as a way to deliver the intervention efficiently, but notably costeffectiveness evaluations comparing groups with the individual approach have not yet been conducted.…”
Section: Sho Okawa Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents’ knowledge of CBT and their role in this type of treatment for their child has been investigated via qualitative measures primarily in the context of parent-delivered CBT or CBT enhanced with a parent training module. Parents commonly endorse initial feelings of surprise when learning about the negative consequences of accommodating their child’s anxiety and endorsed feelings of guilt when practising behaviours such as selective ignoring and carrying out exposures to help their child confront pathological fear (Allard et al ., 2022; Jones, 2017; Pishva, 2017). This ‘paradoxical parenting’ became easier for most parents to implement as they changed roles during their child’s treatment progression from comforters and protectors to supporters and advocates (Allard et al ., 2022; Jones, 2017; Pishva, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Parents commonly endorse initial feelings of surprise when learning about the negative consequences of accommodating their child’s anxiety and endorsed feelings of guilt when practising behaviours such as selective ignoring and carrying out exposures to help their child confront pathological fear (Allard et al ., 2022; Jones, 2017; Pishva, 2017). This ‘paradoxical parenting’ became easier for most parents to implement as they changed roles during their child’s treatment progression from comforters and protectors to supporters and advocates (Allard et al ., 2022; Jones, 2017; Pishva, 2017). After completion of these programmes, parents were also able to identify the nature of anxiety, its relationship with thoughts and physiological symptoms, and have conversations with their child about their anxiety (Jones, 2017; Pishva, 2017).…”
Section: Introductionmentioning
confidence: 99%